A method for preparing a gradient density high absorbency core
Patent Information
- Application Number
- CN202611495289.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-24
- Publication Date
- 2026-10-30
AI Technical Summary
[0006]因此,针对上述问题,本发明提出一种梯度密度高吸收芯体的制备方法,其解决了现有制备工艺无法在成型过程中原位构建有序粒径级配、无法保持隔离导流层湿态孔隙结构、无法实现横向面密度梯度精确控制等技术问题
本发明通过设置干态特征孔径满足D97<d<D3的隔离导流层,在厚度方向上形成小粒径在下、大粒径在上的分级隔离结构,消除了层间粒径突变界面,液体能够沿厚度方向连续传导;
Smart Images

Figure CN122997920A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of disposable sanitary products, in particular to a preparation method of a gradient density high-absorption core body. BACKGROUND
[0002] The absorption core body is the core component of disposable absorbent products such as paper diapers, sanitary napkins, and adult incontinence products. The liquid absorption speed, anti-back seepage performance, and core body utilization rate directly determine the product use quality. The industry has been continuously iterating the core body technology, from the mixed structure of fluff pulp and high molecular water-absorbing resin (SAP) to the composite structure of dust-free paper, fluff pulp, and SAP. At present, the mainstream is the composite core body with non-woven fabric covering SAP particles. The industry has always been pursuing thin, high-SAP-content, and better liquid absorption performance core body products.
[0003] At present, the general composite core body adopts a multi-layer composite structure of an upper absorption layer, an intermediate isolation and flow guide layer, and a lower absorption layer (such as patent CN119499042A). The SAP particles in each layer are applied through independent spreading processes, and the particle sizes of each layer are independently set, resulting in a clear particle size mutation interface between the layers. When liquid penetrates, it is easy to spread horizontally and slow down vertically at the interface. There is no particle size transition structure between the layers, and SAP particles are easy to migrate with the liquid flow, locally accumulate, and even seep out, resulting in high back seepage of the product, small liquid diffusion range, and difficulty for the lower core body to fully play its absorption role, thus the overall core body utilization rate is low.
[0004] To solve the above problems, the existing technology proposes a stepped density and gradient density core body scheme (such as patents CN108670556A and CN114886667A). The density gradient distribution in the thickness direction of SAP is realized by precise feeding in different zones and layers. However, this type of scheme has obvious shortcomings: it relies on multiple sets of spreading equipment for forming, and the gradient structure is fixed after forming, so it cannot construct a continuous transition particle size gradation structure in situ. Moreover, the higher the gradient precision, the more equipment is needed, which greatly increases the process complexity and production cost.
[0005] At the same time, the intermediate flow guide layer of the multi-layer core body has a dilemma in pore size design: if the pore size is too large, the small SAP particles in the lower layer will move upward, disrupting the functional zoning between the layers; if the pore size is too small, it will increase the liquid infiltration resistance and reduce the liquid absorption speed. In addition, the pores of the conventional non-woven fabric flow guide layer are easy to collapse after liquid saturation, the wet-state pore stability is poor, and the flow guide performance continues to decline after repeated liquid absorption, further aggravating the back seepage problem of the product. SUMMARY
[0006] Therefore, in view of the above problems, the present application provides a preparation method of a gradient density high-absorption core body, which solves the technical problems that the existing preparation process cannot construct an ordered particle size gradation in situ during the forming process, cannot maintain the wet-state pore structure of the isolation and flow guide layer, and cannot realize accurate control of the lateral area density gradient.
[0007] To achieve the above objectives, the present invention employs the following technical solution: a method for preparing a gradient density high-absorbency core, wherein the prepared gradient density high-absorbency core comprises a first coating layer, a first absorbent layer, an isolation and diversion layer, a second absorbent layer, and a second coating layer sequentially composited. The first absorbent layer contains first superabsorbent polymer particles with a first particle size distribution, the second absorbent layer contains second superabsorbent polymer particles with a second particle size distribution, the median particle size of the second particle size distribution being larger than the median particle size of the first particle size distribution, and the isolation and diversion layer being a nonwoven fabric with through-pores extending through its thickness direction; the preparation method includes the following steps: S1. Unwind the first covering layer, defining the conveying direction as longitudinal MD and the width direction as transverse CD; S2. The first superabsorbent polymer particles are laid flat on the first coating layer to form the first absorbent layer; S3. The isolation and flow guiding layer is laminated onto the first absorption layer. Before lamination, the isolation and flow guiding layer is subjected to restricted heat shrinkage sizing treatment. The conditions for the restricted heat shrinkage sizing treatment are: tension 3-8 N / m, longitudinal tensile ratio not greater than 1.03, and treatment temperature 130℃-145℃. After treatment, the layer is cooled and shaped. S4. Apply negative pressure suction and low-frequency vibration to the first absorption layer, so that particles with a particle size no greater than d in the first absorption layer pass upward through the through pores, forming a graded transition zone inside the pores of the isolation and flow guiding layer and within a thickness range of ±0.1mm on its upper and lower surfaces; then spread material in sections on the isolation and flow guiding layer to form the second absorption layer, which has a gradient surface density distribution with a high center and low sides along the width direction of the core. S5. Cover the composite second coating layer to obtain a gradient density high-absorption core composite; The through-pores are tapered channels that gradually narrow from the second absorber layer side to the first absorber layer side along the core thickness direction, and the dry characteristic pore diameter d of the through-pores satisfies: D 97 <d<D3,D 97 D3 is the particle size corresponding to 97% of the cumulative volume in the first particle size distribution, and D4 is the particle size corresponding to 3% of the cumulative volume in the second particle size distribution. 97D3 was measured using laser diffraction, and d was measured using the bubble point method; the wet pore size retention rate dwet / ddry of the isolation and guiding layer after being saturated with a 0.9% sodium chloride aqueous solution and drained is not less than 85%, where dwet is the wet characteristic pore size and ddry is the dry characteristic pore size; in the gradation transition zone, the particle mass percentage from the first absorption layer is 2% to 8%, and the particle mass percentage from the second absorption layer is not greater than 1%, and particles with a diameter greater than d in the second absorption layer are intercepted by the isolation and guiding layer and cannot pass through downward.
[0008] Furthermore, the maximum diameter of the tapered channel near the second absorption layer is no greater than 0.95 × D3, and the minimum diameter near the first absorption layer is no less than 1.05 × D3. 97 ; Before step S3, the isolation and diversion layer is punctured from one side using a conical needle, or punctured from both sides using needles with different diameters at both ends, to form the conical channel; the directional liquid diversion ratio Rd of the isolation and diversion layer is not less than 1.3, Rd = tr / tf, tf is the time for 2 mL of sodium chloride aqueous solution with a mass fraction of 0.9% to permeate forward, and tr is the time for 2 mL of reverse permeation.
[0009] Furthermore, the restricted heat shrinkage sizing treatment in step S3 ensures that the wet pore size retention rate (dwet / ddry) of the isolation and flow guiding layer is 85% to 95%; the wet pore size retention rate of the isolation and flow guiding layer after three liquid absorption-draining cycles is not less than 80%; and the wet thickness retention rate of the isolation and flow guiding layer under a 2 kPa compressive load is not less than 90%.
[0010] Furthermore, the water retention capacity of the first superabsorbent polymer particles is not less than 33 g / g, and the salt water absorption rate is not greater than 35 s; the dry conductivity of the second superabsorbent polymer particles is not less than 60 × 10⁻⁶. -7 The wet-to-dry conductivity ratio after three liquid absorptions is not less than 0.60; wherein, the dry conductivity of the second superabsorbent polymer particles is more than 2.0 times that of the first superabsorbent polymer particles, and the water retention capacity of the first superabsorbent polymer particles is more than 1.10 times that of the second superabsorbent polymer particles.
[0011] Furthermore, in step S4, at least three independent feeding ports are set along the transverse CD direction of the core for zoned material distribution. The amount of material dropped from the central feeding port is 1.6 to 2.6 times that of the feeding ports on both sides, so that the surface density of the central area of the second absorption layer is 1.6 to 2.6 times that of the surface density of the edge areas on both sides. The second covering layer is a non-woven fabric with printed reference marks. In step S5, the printed reference marks are used as positioning references for lamination, so that the alignment deviation between the high absorption area in the center of the core and the center of the printed reference marks does not exceed ±1mm.
[0012] Furthermore, the isolation and diversion layer is a polypropylene hot air nonwoven fabric or a perforated nonwoven fabric, and its fibers are polypropylene fibers or polypropylene / polyethylene bicomponent fibers; the restricted heat shrinkage sizing treatment time in step S3 is 45 to 75 seconds.
[0013] Furthermore, the negative pressure suction pressure in step S4 is -0.8 kPa to -1.5 kPa, and the frequency of the low-frequency vibration is 30 to 40 Hz.
[0014] Furthermore, after the graded transition zone is formed, the first superabsorbent polymer particles penetrate upward through the isolation and guiding layer and accumulate in the graded transition zone, with the mass percentage of the first superabsorbent polymer particles further penetrating upward into the main body of the second absorbent layer not exceeding 1%; the mass percentage of the second superabsorbent polymer particles penetrating downward through the isolation and guiding layer into the first absorbent layer and the lower surface of the isolation and guiding layer not exceeding 0.1%. Along the thickness direction of the core, the mass fraction of the first superabsorbent polymer particles decreases continuously and monotonically from the first absorbent layer to the second absorbent layer, with no discrete particle clusters or abrupt particle size interfaces between the layers.
[0015] By adopting the aforementioned technical solution, the beneficial effects of the present invention are: This invention satisfies D by setting the dry-state characteristic aperture. 97 The isolation and flow guiding layer with <d<D3 forms a hierarchical isolation structure with small particle size at the bottom and large particle size at the top in the thickness direction, which eliminates the abrupt particle size interface between layers, and the liquid can be continuously conducted along the thickness direction. The wet pore size retention rate of the isolation and diversion layer is not less than 85%, and the through pores still maintain diversion capacity after liquid saturation, thus inhibiting backflow caused by wet pore collapse; Within the graded transition zone, the particle mass percentage from the first absorption layer is 2% to 8%, and the particle mass percentage from the second absorption layer is no more than 1%. This forms a particle enrichment zone with a continuous transition in particle size within the isolation and guiding layer, avoiding interlayer discrete particle clusters and abrupt particle size interfaces, which is conducive to the continuous transfer of liquid from the gaps between large particles in the upper layer to the small particle accumulation in the lower layer. The second absorbent layer has a gradient surface density distribution along the width of the core, with a high center and low sides. This allows the liquid to be rapidly absorbed in the high absorption area in the center of the core and conducted along the thickness direction, reducing side leakage and edge waste caused by the liquid spreading to the sides. The through-pores are tapered channels that gradually narrow from the second absorbent layer side to the first absorbent layer side, giving the isolation and guiding layer the ability to direct liquid flow, and inhibiting the reverse backflow of liquid in the wet state. The preparation method uses restricted heat shrinkage sizing treatment to shape the pores of nonwoven fabric, and then uses negative pressure suction and low frequency vibration to drive the controlled upward migration of small-diameter particles. This can stably form a gradation transition zone in the isolation and guiding layer, and achieve a continuous monotonous distribution of particles along the thickness direction, thereby improving manufacturing consistency and product qualification rate. Attached Figure Description
[0016] Figure 1 This is a schematic diagram of the layered structure of the gradient density high-absorption core of the present invention; Figure 2 This is a partially enlarged schematic diagram of the conical channels in the isolation and flow guiding layer of the present invention; Figure 3 This is a schematic diagram of the gradient surface density distribution of the second absorption layer along the width direction of the core in this invention; Figure 4 This is a flowchart of the preparation method of the gradient density high-absorbency core of the present invention; In the figure: Second absorbent layer-1, Second coating layer-2, Isolation and diversion layer-3, First absorbent layer-4, First coating layer-5, Gradation transition zone-6, Second superabsorbent polymer particles-11, Conical channel-31, Maximum end-32, Minimum end-33, First superabsorbent polymer particles-41. Detailed Implementation
[0017] The present invention will now be further described in conjunction with the accompanying drawings and specific embodiments. Example 1
[0018] refer to Figures 1-4 As shown, the gradient density high-absorbent core of this embodiment includes a first coating layer 5, a first absorbent layer 4, an isolation and diversion layer 3, a second absorbent layer 1, and a second coating layer 2, which are sequentially composited.
[0019] The first superabsorbent polymer (SAP) particle 41 is a surface-crosslinked sodium polyacrylate resin, prepared by aqueous solution polymerization and subjected to surface crosslinking treatment; the second superabsorbent polymer (SAP) particle 11 is a large-particle-size resin that has been screened and air-classified, with an overall particle size larger than the first SAP particle 41.
[0020] The first coating layer 5 is a hydrophilic hot-air nonwoven fabric with a density of 18 g / m²; the first absorbent layer 4 has a surface density of 200 g / m², wherein the first superabsorbent polymer particles 41 have a density of 160 g / m², and the particle size distribution of the first superabsorbent polymer particles 41 is D. 50 300μm, D 97 Its diameter is 560 μm, water retention capacity is 36 g / g, brine absorption rate is 28 s, and dry conductivity is 35 × 10⁻⁶. -7 cm³·s / g. The areal density of the second absorbent layer 1 is gradient-distributed along the width of the core. The areal density of the central region is 340 g / m², of which the second superabsorbent polymer particles 11 are 280 g / m². The areal density of the two edge regions is 155 g / m², of which the second superabsorbent polymer particles 11 are 120 g / m². The areal density of the central region is 2.19 times that of the edge regions. The particle size distribution of the second superabsorbent polymer particles 11 is D3 = 640 μm, D... 50 Its diameter is 740 μm, water retention capacity is 30 g / g, and dry conductivity is 85 × 10⁻⁶. -7 The wet-to-dry conductivity ratio after three cycles of absorption and draining is 0.68. The dry conductivity of the second superabsorbent polymer particles 11 is 2.43 times that of the first superabsorbent polymer particles 41, and the water retention capacity of the first superabsorbent polymer particles 41 is 1.20 times that of the second superabsorbent polymer particles 11. The second absorbent layer 1 exhibits a gradient surface density distribution with a high concentration in the middle and low concentrations on both sides along the width of the core. The alignment deviation between the central high-absorbency area and the center of the printed reference mark is 0.4 mm.
[0021] The isolation and diversion layer 3 is made of polypropylene hot-air nonwoven fabric or perforated nonwoven fabric, and the fibers are polypropylene fibers or polypropylene / polyethylene bicomponent fibers. The through-pores of the isolation and diversion layer 3 are tapered channels 31 that gradually narrow from the second absorbent layer side to the first absorbent layer side in the thickness direction. The tapered channels 31 are formed before lamination: the isolation and diversion layer 3 is punctured from one side using a tapered needle, or perforated from both sides of the isolation and diversion layer 3 using needles with different diameters at both ends, to form the tapered channels 31. Subsequently, the isolation and diversion layer 3 undergoes restricted heat shrinkage sizing treatment: the nonwoven fabric is conveyed through the hot air treatment zone under the conditions of 3-8 N / m tension and longitudinal tensile ratio not greater than 1.03, and then heat-treated at 130℃-145℃ for 30-90s before cooling and shaping, so that the tapered channels 31 are shaped into a stable pore size structure in the thickness direction. The maximum pore diameter 32 near the second absorption layer and the minimum pore diameter 33 near the first absorption layer satisfy the following conditions: the maximum pore diameter 32 is not greater than 0.95 times D3, and the minimum pore diameter 33 is not less than D3. 971.05 times. In this embodiment, the isolation and diversion layer 3 is a 40g / m² PP hot air nonwoven fabric with a thickness of 0.55mm. The fiber is polypropylene fiber. A conical channel 31 is formed by piercing from one side using a conical needle. The restricted heat shrinkage sizing treatment conditions are: tension 5N / m, longitudinal tensile ratio 1.02, treatment temperature 135℃, and treatment time 60s. After treatment, it is cooled and shaped.
[0022] The measured dry characteristic pore size d is 597 μm, which satisfies D. 97 <d<D3; the maximum end 32 of the conical channel 31 has a diameter of 600 μm, and the minimum end 33 has a diameter of 595 μm. The wet pore size retention rate is 90%, and after three liquid absorption-draining cycles, the wet pore size retention rate is 84%. The wet thickness retention rate under a 2 kPa compressive load is 93%, and the directional liquid guiding ratio Rd=1.6, where tf=18s and tr=28.8s. After the above sizing treatment, the wet pore size retention rate, the wet pore size retention rate after three cycles, and the wet thickness retention rate under a 2 kPa compressive load of the isolation guiding layer 3 all meet the requirements of this application.
[0023] The core preparation method in this embodiment includes the following steps: S1. Unwind the first covering layer 5, defining the conveying direction as longitudinal MD and the width direction as transverse CD; S2. First superabsorbent polymer particles 41 are applied to the first coating layer 5 by spreading the material using a spreading device to form the first absorbent layer 4. S3. The isolation and flow guiding layer 3, which has undergone restricted heat shrinkage and sizing treatment, is composited onto the first absorption layer 4; S4. Apply a negative pressure of -1.0 kPa to the bottom of the first coating layer 5, and at the same time apply low-frequency vibration to the first absorption layer 4 with an amplitude of 1 mm and a frequency of 35 Hz, so that small particles with a particle size of no more than 597 μm in the first absorption layer 4 pass upward through the through-pores of the isolation and guiding layer 3, forming a graded transition zone 6 in the pores of the isolation and guiding layer 3 and in the 0.1 mm thickness range on its upper and lower surfaces; then, spread material in sections on the isolation and guiding layer 3 with three horizontally arranged independent feeding ports, with the material falling from the central feeding port being 2.19 times the material falling from the two side feeding ports, forming a second absorption layer 1 with a horizontal gradient distribution; S5. The second coating layer 2, which covers the composite tape with printed reference marks, is used as the positioning reference. The printed reference marks are identified by a vision inspection device and aligned with the central high absorption area to complete the composite, resulting in a gradient density high absorption core composite.
[0024] In this embodiment, the mass percentage of particles from the first absorbent layer 4 in the gradation transition zone 6 is 5.2%, and the mass percentage of particles from the second absorbent layer 1 is 0.3%. The mass percentage of the first superabsorbent polymer particles 41 that further penetrate upward into the main body of the second absorbent layer 1 is 0.4%. The mass percentage of the second superabsorbent polymer particles 11 that penetrate downward through the isolation and guiding layer 3 into the first absorbent layer 4 and the lower surface of the isolation and guiding layer 3 is 0.05%. Along the thickness direction, the mass fraction of the first superabsorbent polymer particles 41 decreases continuously and monotonically from the first absorbent layer 4 to the second absorbent layer 1, with no discrete particle clusters or abrupt particle size interfaces between layers.
[0025] The performance of the core obtained in Example 1 was tested, and the results are as follows: 5mL absorption time was 8.2s, reabsorption amount was 2.0g, liquid diffusion length was 132mm, core utilization rate was 93%, and leakage amount was 0g. Example 2
[0026] The difference between this embodiment and Embodiment 1 is that the overall values of the parameters and process parameters of each layer are at the lower end of the scope of this application.
[0027] The areal density of the first absorbent layer 4 is 180 g / m², of which the first superabsorbent polymer particles 41 have a density of 145 g / m² and a particle size distribution of D. 50 280μm, D 97 Its diameter is 520 μm, water retention capacity is 35 g / g, brine absorption rate is 32 s, and dry conductivity is 34 × 10⁻⁶. - 7 cm³·s / g. The surface density of the central region of the second absorbent layer 1 is 320 g / m², of which the second superabsorbent polymer particles 11 are 260 g / m². The surface density of the two edge regions is 200 g / m², of which the second superabsorbent polymer particles 11 are 160 g / m². The surface density of the central region is 1.6 times that of the edge region. The particle size distribution of the second superabsorbent polymer particles 11 is D3 = 600 μm, D... 50 It has a diameter of 700 μm, a water retention capacity of 29.5 g / g, and a dry conductivity of 72 × 10⁻⁶. -7 The wet-to-dry conductivity ratio after three absorption-drain cycles is 0.62 (cm³·s / g). The dry conductivity of the second superabsorbent polymer particle 11 is 2.12 times that of the first superabsorbent polymer particle 41, and the water retention capacity of the first superabsorbent polymer particle 41 is 1.19 times that of the second superabsorbent polymer particle 11. The alignment deviation between the central high-absorption area and the center of the printed reference mark is 0.8 mm.
[0028] The isolation and flow guiding layer 3 is a 35 g / m² PP hot-air nonwoven fabric with a thickness of 0.50 mm. Conical channels 31 are formed by perforating both sides using needles with different apertures at both ends. Subsequently, it undergoes restricted heat shrinkage sizing treatment under the following conditions: tension 3 N / m, longitudinal tensile ratio 1.01, treatment temperature 130℃, and treatment time 45 s. The measured dry characteristic pore size d is 558 μm, satisfying D... 97 <d<D3; the maximum end 32 of the conical channel 31 has a diameter of 565μm, and the minimum end 33 has a diameter of 552μm. The wet pore size retention rate is 85%, and after three liquid absorption-draining cycles, the wet pore size retention rate is 80%. Under a 2kPa compression load, the wet thickness retention rate is 91%, and the directional liquid guiding ratio Rd=1.3, where tf=22s and tr=28.6s.
[0029] During preparation, the negative pressure suction pressure is -0.8 kPa, and the low-frequency vibration frequency is 30 Hz. Three horizontally arranged independent feeding ports are used for zoned feeding, with the central feeding port discharging 1.6 times the amount discharging from the two side feeding ports. In the gradation transition zone 6, the particle mass percentage from the first absorbent layer 4 is 2.1%, and the particle mass percentage from the second absorbent layer 1 is 0.2%. The mass percentage of the first superabsorbent polymer particles 41 further penetrating upwards into the main body of the second absorbent layer 1 is 0.3%. The mass percentage of the second superabsorbent polymer particles 11 penetrating downwards through the isolation and guiding layer 3 into the first absorbent layer 4 and the lower surface of the isolation and guiding layer 3 is 0.03%.
[0030] The performance of the core obtained in Example 2 was tested, and the results are as follows: the liquid absorption time of 5mL was 10.5s, the reabsorption amount was 2.6g, the liquid diffusion length was 124mm, the core utilization rate was 90%, and the leakage amount was 0g. Example 3
[0031] The difference between this embodiment and Embodiment 1 is that the parameters of each layer and the overall process parameters are taken at the high end of the scope of this application.
[0032] The areal density of the first absorbent layer 4 is 220 g / m², of which the first superabsorbent polymer particles 41 have a density of 180 g / m² and a particle size distribution of D. 50 320μm, D 97 Its diameter is 600 μm, water retention capacity is 37 g / g, salt water absorption rate is 25 s, and dry conductivity is 38 × 10⁻⁶. - 7cm³·s / g. The surface density of the central region of the second absorbent layer 1 is 355 g / m², of which the second superabsorbent polymer particles 11 account for 295 g / m². The surface density of the two edge regions is 138 g / m², of which the second superabsorbent polymer particles 11 account for 108 g / m². The surface density of the central region is 2.57 times that of the edge regions. The particle size distribution of the second superabsorbent polymer particles 11 is D3 of 680 μm and D50 of 780 μm. The water retention capacity is 31 g / g, and the dry conductivity is 95 × 10⁻⁶. -7 The wet-to-dry conductivity ratio after three absorption-drain cycles is 0.71 (cm³·s / g). The dry conductivity of the second superabsorbent polymer particle 11 is 2.5 times that of the first superabsorbent polymer particle 41, and the water retention capacity of the first superabsorbent polymer particle 41 is 1.19 times that of the second superabsorbent polymer particle 11. The alignment deviation between the central high-absorption area and the center of the printed reference mark is 0.3 mm.
[0033] The isolation and diversion layer 3 is a 45 g / m² PP hot-air nonwoven fabric with a thickness of 0.60 mm. Conical channels 31 are formed by unilateral puncture using a conical needle, followed by restricted heat shrinkage sizing treatment. The treatment conditions are: tension 8 N / m, longitudinal tensile ratio 1.03, treatment temperature 145℃, and treatment time 75 s. The measured dry characteristic pore size d is 640 μm, satisfying D... 97 <d<D3; the maximum end 32 of the conical channel 31 has a diameter of 645μm, and the minimum end 33 has a diameter of 633μm. The wet pore size retention rate is 95%, and after three liquid absorption-draining cycles, the wet pore size retention rate is 88%. The wet thickness retention rate under a 2kPa compression load is 95%, and the directional liquid guiding ratio Rd=1.8, where tf=16s and tr=28.8s.
[0034] During preparation, the negative pressure suction pressure is -1.5 kPa, and the low-frequency vibration frequency is 40 Hz. Three horizontally arranged independent feeding ports are used for zoned feeding, with the central feeding port discharging 2.57 times the amount discharging from the two side feeding ports. In the gradation transition zone 6, the particle mass percentage from the first absorbent layer 4 is 7.6%, and the particle mass percentage from the second absorbent layer 1 is 0.6%. The mass percentage of the first superabsorbent polymer particles 41 further penetrating upwards into the main body of the second absorbent layer 1 is 0.6%. The mass percentage of the second superabsorbent polymer particles 11 penetrating downwards through the isolation and guiding layer 3 into the first absorbent layer 4 and the lower surface of the isolation and guiding layer 3 is 0.08%.
[0035] The performance of the core obtained in Example 3 was tested, and the results are as follows: the liquid absorption time of 5 mL was 7.5 s, the reabsorption amount was 1.7 g, the liquid diffusion length was 138 mm, the core utilization rate was 95%, and the leakage amount was 0 g.
[0036] Comparative Example 1 In this comparative example, the isolation and flow guiding layer 3 is not set. The first absorption layer 4 and the second absorption layer 1 are directly composited. The remaining structure and preparation conditions are the same as in Example 1.
[0037] Test results: 5mL aspiration time was 19.6s, reabsorption amount was 8.5g, liquid diffusion length was 74mm, core utilization rate was 68%, and leakage amount was 3.6g.
[0038] Because there is no isolation structure between the layers, the particle size of the particles in the upper and lower layers changes abruptly at the interface, the lateral spread of the liquid at the interface is hindered, and the large particles in the upper layer migrate to the edge with the liquid and seep out locally.
[0039] Comparative Example 2 In this comparative example, the isolation and diversion layer 3 is replaced by a perforated membrane with a dry characteristic pore size d of 700 μm. This pore size is larger than the D3 of the second superabsorbent polymer particle 11, which is 640 μm. The remaining structure and preparation conditions are the same as in Example 1.
[0040] Test results: 5mL aspiration time was 14.3s, reabsorption amount was 6.2g, liquid diffusion length was 96mm, core utilization rate was 72%, and leakage amount was 5.4g.
[0041] Because the pore size exceeds the upper limit, the downward permeability of the second superabsorbent polymer particles 11 increases. The mass ratio of particles from the second absorbent layer 1 in the graded transition zone 6 reaches 4.2%, and the mass ratio of the second superabsorbent polymer particles 11 penetrating into the lower surface of the first absorbent layer 4 and the isolation and guiding layer 3 reaches 1.5%. The second absorbent layer 1 has local material shortage, forming voids and serious particle leakage.
[0042] Comparative Example 3 The comparative example isolation and diversion layer 3 is made of fine spunbond nonwoven fabric with a dry characteristic pore size d of 500 μm. This pore size is smaller than the D of the first superabsorbent polymer particles 41. 97 The thickness is 560 μm, and the rest of the structure and preparation conditions are the same as in Example 1.
[0043] Test results: 5mL aspiration time was 41s, reabsorption amount was 4.9g, liquid diffusion length was 82mm, core utilization rate was 74%, and leakage amount was 0g.
[0044] Because the pore size is below the lower limit, the first superabsorbent polymer particles 41 cannot migrate upwards. The mass ratio of particles from the first absorbent layer 4 in the graded transition zone 6 is only 0.8%, and the graded transition zone is not formed. The particles below the isolation and guiding layer 3 are densely packed and the gel is blocked, resulting in a significant decrease in the liquid absorption rate.
[0045] Comparative Example 4 The comparative example isolation and flow guiding layer 3 uses ordinary PP spunbond nonwoven fabric without restricted heat shrinkage sizing treatment. The dry characteristic pore size d is 598 μm, and the wet pore size retention rate is only 62%. The remaining structure and preparation conditions are the same as in Example 1.
[0046] Test results: 5mL aspiration time was 11.8s, reabsorption amount was 5.7g, liquid diffusion length was 105mm, core utilization rate was 81%, and leakage amount was 0.9g; after three aspiration-draining cycles, the wet pore size retention rate dropped to 45%, the wet thickness retention rate under 2kPa compression load was only 70%, and the liquid diffusion length decreased by 35% after repeated aspiration compared to the first time.
[0047] Because the pores are not well-defined, the channels collapse in the wet state, and the conductivity continues to decrease after repeated liquid absorption.
[0048] Comparative Example 5 The isolation and flow guiding layer 3 in this comparative example is a PP hot air nonwoven fabric with the same amount of material as in Example 1. The opening process forms straight cylindrical holes with consistent pore diameter along the thickness direction. The pores have no taper and the dry characteristic pore diameter d is 597 μm. The remaining structure and preparation conditions are the same as in Example 1.
[0049] Test results: The directional liquid ratio Rd was 1.02 (tf=28.2s, tr=28.8s), the 5mL absorption time was 9.8s, the reabsorption amount was 3.9g, the liquid diffusion length was 121mm, the core utilization rate was 86%, and the leakage amount was 0.2g.
[0050] Because the channels are not tapered, the resistance to forward and reverse osmosis of the liquid is similar, and no directional liquid guiding ability is formed. Under wet conditions, the reverse osmosis of liquid from the second absorbent layer to the first absorbent layer increases, and the amount of backflow is higher than in Example 1.
[0051] Comparative Example 6 In this comparative example, the material is fed into the three feed ports in equal amounts in step S4. The surface density of the second absorbent layer 1 is uniformly distributed along the width of the core. The surface density of the central area and the edge area is about 250 g / m². No gradient surface density distribution with a high center and low sides is formed. The remaining structure and preparation conditions are the same as in Example 1.
[0052] Test results: 5mL aspiration time was 10.2s, reabsorption amount was 4.6g, liquid diffusion length was 149mm, core utilization rate was 77%, and leakage amount was 0.8g.
[0053] Since the surface density of the center and the edge of the second absorption layer 1 is the same, a central high absorption zone is not formed. The liquid is evenly distributed along the width of the core and diffuses to both sides of the edge. The liquid at the edge cannot be quickly concentrated and absorbed, resulting in a decrease in the core utilization rate and an increase in edge leakage.
[0054] Summary of performance test results Table 1. Core performance test results of the examples and comparative examples.
[0055] The test results above show that only when the dry characteristic aperture d of the isolation guide layer 3 satisfies D 97 <d<D3, wet pore size retention rate is not less than 85%, the through pores are tapered channels that gradually shrink from the second absorbent layer side to the first absorbent layer side and form a graded transition zone 6, when the second absorbent layer 1 has a gradient surface density distribution with high in the middle and low on both sides, the core can simultaneously obtain a faster liquid absorption rate, a lower re-permeation amount and a higher core utilization rate.
[0056] Resin particle performance testing: Particle size distribution was determined by laser diffraction (refer to ISO 13320) using a dry dispersion method. The particle sizes D3 and D4 corresponding to 3%, 50%, and 97% of the cumulative volume were recorded. 50 D 97 Water retention capacity was determined by centrifugal water retention method; brine absorption rate was determined by eddy disappearance method; dry conductivity and wet-dry conductivity ratio after three liquid absorption-drainage cycles were determined by flow tube method.
[0057] Performance testing of the isolation and guiding layer: The dry and wet characteristic pore diameters were determined by the bubble point method (refer to ASTM F316), and the wet pore diameter retention rate was the ratio of the wet characteristic pore diameter to the dry characteristic pore diameter; the wet thickness retention rate was determined under a 2 kPa compressive load; the directional liquid guiding ratio was determined by the liquid guiding tube permeation method; the morphology of the conical channel and the diameters at both ends were determined by microscopic observation after freezing sections in the thickness direction.
[0058] Core structure testing: Surface density is measured by sampling and weighing, and the surface density of the central area and the two side edge areas is measured in sections along the width direction of the core; alignment deviation is measured with the center of the printed reference mark as the reference; particle distribution in the gradation transition zone is measured by freezing, sieving and weighing in the thickness direction.
[0059] Core performance testing: Liquid absorption rate, reabsorption rate, diffusion length, core utilization rate and leakage rate are determined according to conventional core performance testing methods.
[0060] It should be noted that those skilled in the art will understand that the amount of superabsorbent polymer particles applied in the first absorbent layer 4 and the second absorbent layer 1, the amount and thickness of the isolation and diversion layer 3, and the areal density ratio of the central and edge regions of the second absorbent layer 1 can all be adjusted within the range described in this application. The superabsorbent polymer particles can also be other commonly used types such as potassium polyacrylate, starch grafted, or cellulose grafted. As long as they adopt a structure of sequentially compounded first coating layer, first absorbent layer, isolation and diversion layer, second absorbent layer, and second coating layer, and satisfy the characteristic combination of pore size classification, graded transition zone, and gradient areal density distribution of the isolation and diversion layer, the technical effects of this application can be achieved.
[0061] The above embodiments are merely preferred embodiments of the present invention and do not constitute a limitation on the present invention. All equivalent modifications made by those skilled in the art based on the technical solutions disclosed in this application are within the scope of protection claimed in this application.
Claims
1. A method for preparing a gradient density high-absorbency core, wherein the prepared gradient density high-absorbency core comprises a first coating layer, a first absorbent layer, an isolation and diversion layer, a second absorbent layer, and a second coating layer sequentially composited, wherein the first absorbent layer comprises first superabsorbent polymer particles with a first particle size distribution, the second absorbent layer comprises second superabsorbent polymer particles with a second particle size distribution, the median particle size of the second particle size distribution being larger than the median particle size of the first particle size distribution, and the isolation and diversion layer is a nonwoven fabric with through-pores extending through its thickness direction; characterized in that, The preparation method includes the following steps: S1. Unwind the first covering layer, defining the conveying direction as longitudinal MD and the width direction as transverse CD; S2. The first superabsorbent polymer particles are laid flat on the first coating layer to form the first absorbent layer; S3. The isolation and flow guiding layer is laminated onto the first absorption layer. Before lamination, the isolation and flow guiding layer is subjected to restricted heat shrinkage sizing treatment. The conditions for the restricted heat shrinkage sizing treatment are: tension 3-8 N / m, longitudinal tensile ratio not greater than 1.03, treatment temperature 130℃-145℃, treatment time 30-90s, and cooling and shaping after treatment. S4. Apply negative pressure suction and low-frequency vibration to the first absorption layer, so that particles with a particle size no greater than d in the first absorption layer pass upward through the through pores, forming a graded transition zone inside the pores of the isolation and flow guiding layer and within a thickness range of ±0.1mm on its upper and lower surfaces; then spread material in sections on the isolation and flow guiding layer to form the second absorption layer, which has a gradient surface density distribution with a high center and low sides along the width direction of the core. S5. Cover the composite second coating layer to obtain a gradient density high-absorption core composite; The through-pores are tapered channels that gradually narrow from the second absorber layer side to the first absorber layer side along the core thickness direction, and the dry characteristic pore diameter d of the through-pores satisfies: D 97 <d<D3,D 97 D3 is the particle size corresponding to 97% of the cumulative volume in the first particle size distribution, and D4 is the particle size corresponding to 3% of the cumulative volume in the second particle size distribution. 97 D3 was measured using laser diffraction, and d was measured using the bubble point method; the wet pore size retention rate dwet / ddry of the isolation and guiding layer after being saturated with a 0.9% sodium chloride aqueous solution and drained is not less than 85%, where dwet is the wet characteristic pore size and ddry is the dry characteristic pore size; in the gradation transition zone, the particle mass percentage from the first absorption layer is 2% to 8%, and the particle mass percentage from the second absorption layer is not greater than 1%, and particles with a diameter greater than d in the second absorption layer are intercepted by the isolation and guiding layer and cannot pass through downward.
2. The method for preparing a gradient density high-absorbency core according to claim 1, characterized in that: The maximum diameter of the tapered channel near the second absorption layer is no greater than 0.95 × D3, and the minimum diameter near the first absorption layer is no less than 1.05 × D3. 97 ; Before step S3, the isolation and diversion layer is punctured from one side using a conical needle, or punctured from both sides using needles with different diameters at both ends, to form the conical channel; the directional liquid diversion ratio Rd of the isolation and diversion layer is not less than 1.3, Rd = tr / tf, tf is the time for 2 mL of sodium chloride aqueous solution with a mass fraction of 0.9% to permeate forward, and tr is the time for 2 mL of reverse permeation.
3. The method for preparing a gradient density high-absorbency core according to claim 1, characterized in that: The restricted heat shrinkage sizing treatment in step S3 ensures that the wet pore size retention rate (dwet / ddry) of the isolation and guide layer is 85% to 95%; the wet pore size retention rate of the isolation and guide layer after three liquid absorption-draining cycles is not less than 80%; and the wet thickness retention rate of the isolation and guide layer under a 2 kPa compressive load is not less than 90%.
4. The method for preparing a gradient density high-absorbency core according to claim 1, characterized in that: The first superabsorbent polymer (SAP) particles have a water retention capacity of not less than 33 g / g and a salt water absorption rate of not more than 35 s; the second SAP particles have a dry conductivity of not less than 60 × 10⁻⁶. -7 The wet-to-dry conductivity ratio after three liquid absorptions is not less than 0.60; wherein, the dry conductivity of the second superabsorbent polymer particles is more than 2.0 times that of the first superabsorbent polymer particles, and the water retention capacity of the first superabsorbent polymer particles is more than 1.10 times that of the second superabsorbent polymer particles.
5. The method for preparing a gradient density high-absorbency core according to claim 1, characterized in that: In step S4, at least three independent feeding ports are set along the transverse CD direction of the core for zoned material distribution. The amount of material dropped from the central feeding port is 1.6 to 2.6 times that of the feeding ports on both sides, so that the surface density of the central area of the second absorption layer is 1.6 to 2.6 times that of the surface density of the edge areas on both sides. The second covering layer is a non-woven fabric with printed reference marks. In step S5, the printed reference marks are used as positioning references for composite bonding, so that the alignment deviation between the high absorption area in the center of the core and the center of the printed reference marks does not exceed ±1mm.
6. The method for preparing a gradient density high-absorbency core according to claim 1, characterized in that: The isolation and flow guiding layer is a polypropylene hot air nonwoven fabric or a perforated nonwoven fabric, and its fibers are polypropylene fibers or polypropylene / polyethylene bicomponent fibers; the restricted heat shrinkage sizing treatment time in step S3 is 45 to 75 seconds.
7. The method for preparing a gradient density high-absorbency core according to claim 1, characterized in that: The negative pressure suction pressure in step S4 is -0.8 kPa to -1.5 kPa, and the frequency of the low-frequency vibration is 30 to 40 Hz.
8. The method for preparing a gradient density high-absorbency core according to claim 1, characterized in that: After the graded transition zone is formed, the first superabsorbent polymer particles penetrate upward through the isolation and guiding layer and accumulate in the graded transition zone, with the mass percentage of the first superabsorbent polymer particles further penetrating upward into the main body of the second absorbent layer not exceeding 1%; the mass percentage of the second superabsorbent polymer particles penetrating downward through the isolation and guiding layer into the first absorbent layer and the lower surface of the isolation and guiding layer not exceeding 0.1%. Along the thickness direction of the core, the mass fraction of the first superabsorbent polymer particles decreases continuously and monotonically from the first absorbent layer to the second absorbent layer, with no discrete particle clusters or abrupt particle size interfaces between the layers.
Citation Information
Patent Citations
Composite core with gradient density and preparation method and application thereof
CN108670556A
Novel absorption core forming process
CN114886667A
